LINC01001 Promotes Progression of Crizotinib-Resistant NSCLC by Modulating IGF2BP2/MYC Axis - Meiling Zhang; Qian Wang; Zihao Ke; Yijing Liu; Huijin Guo; Shencun Fang; Kaihua Lu (Frontiers Media S.A., 2021)
Background: Crizotinib is a microtubule-related protein-4-anaplastic lymphoma kinase (EML4-ALK) multi-target tyrosine kinase inhibitor applied in the treatment of ALK-rearranged NSCLC. However, the specific molecular mechanism underlying its therapeutic effect remains unclear. Therefore, the purpose of this research is to explore the mechanism by which crizotinib targets NSCLC with ALK-rearrangement, mainly whether it is related to LINC01001 in regulating NSCLC progression via IGF2BP2/MYC axis.Methods: RT-qPCR is conducted to evaluate the mRNA levels of LINC01001, IGF2BP2 and MYC in A549/R and H1299/R cells. CCK-8 and EdU assays are performed to assess the viability and proliferation of A549/R and H1299/R cells. Western blot is conducted to measure the levels of PCNA and Ki-67 proteins in A549/R and H1299/R cells. FACs and TUNEL are performed to detect apoptosis of A549/R and H1299/R cells. Immunohistochemical staining is performed to assess the levels of Ki67 in crizotinib-resistant NSCLC tissue. Bioinformatics analysis of multiple CLIP (crosslinking-immunoprecipitation) data found potential binding sites between LINC01001 and IGF2BP2, IGF2BP2 and MYC, that are confirmed by RIP assay and RNA pulldown assay.Results: Our findings illustrated that LINC01001 is highly expressed in crizotinib-resistant NSCLC cells and associated with poor overall survival of NSCLC patients. Inhibition of LINC01001 depresses crizotinib resistance of NSCLC cells. LINC01001 interacts with IGF2BP2, and inhibition of IGF2BP2 depresses crizotinib resistance of NSCLC cells. IGF2BP2 interacts with the mRNA of MYC, and LINC01001 overexpression increases crizotinib resistance of NSCLC via MYC.Conclusion: LINC01001 promotes the progression of crizotinib-resistant NSCLC by modulating the IGF2BP2/MYC axis. Our research clarifies the specific mechanism of crizotinib-resistance in NSCLC treatment.